Zygosaccharomyces rouxii Trk1 is an efficient potassium transporter providing yeast cells with high lithium tolerance - Zimmermannova, Olga; Salazar, Ana; Sychrova, Hana; Ramos, Jose (FEMS yeast research, 2015)
Zygosaccharomyces rouxii is an osmotolerant yeast growing in the presence of high concentrations of salts and/or sugars. The maintenance of intracellular potassium homeostasis is essential for osmostress adaptation. Zygosaccharomyces rouxii is endowed with only one typical potassium transporter (ZrTrk1). We characterized ZrTrk1 activity and its contribution to various physiological parameters in detail. Our results show that ZrTrk1 is a high-affinity K(+) transporting system efficiently discriminating between K(+) and Li(+) and indicate the presence of another, currently unknown K(+) importing system with a low affinity in Z. rouxii cells. Upon ZrTrk1 heterologous expression in Saccharomyces cerevisiae, it confers cells with a remarkably high lithium tolerance (even to wild-type strains) due to preventing Li(+) influx into cells, and is able to complement a plasma-membrane hyperpolarization and cell sensitivity to cationic compounds caused by the lack of endogenous K(+) transporters. Intracellular pH measurements with pHluorin, whose coding sequence was integrated into the genome, showed that the expression of ZrTrk1 also complements a decrease in intracellular pH in S. cerevisiae trk1Δ trk2Δ cells. Our data corroborate a tight connection between potassium and proton transporters in yeasts and provide new insights into Z. rouxii cation homeostasis and the basis of its high osmotolerance.
Keywords: exprese genu; Gene Expression; Potassium; draslík; Drug Tolerance; Saccharomyces cerevisiae; intracellular pH; lithium; Hydrogen-Ion Concentration; cytosol; Cation Transport Proteins; Zygosaccharomyces rouxii; potassium transport; tolerance léku; Lithium; membrane potential; Cytosol; koncentrace vodíkových iontů; Zygosaccharomyces; pHluorin integration; lithium tolerance; proteiny přenášející kationty